Canadian securities lending market ecology - Jesse Johal; Joanna Roberts; John Sim (Bank of Canada, 2019)
This is the fourth of the Financial Markets Department's descriptions of Canadian financial industrial organization. The paper discusses the organization of the securities lending market in Canada. We outline key characteristics of securities lending contracts, participants in the securities lending market, the market infrastructures that support securities lending activities, and aggregated statistics describing the Canadian market. We also describe trading practices, risks and regulation relating to the securities lending market. A securities lending transaction is the collateralized and temporary transfer of ownership of a security for a fee. One party to the transaction lends securities and collects a fee for the loan. The other party borrows securities and pays the fee. The securities borrower secures the loan by pledging collateral, such as cash or other securities. The main participants in the Canadian securities lending market are banks, dealers, investment funds (e.g., pension funds, mutual funds) and custodian banks. Securities lending supports a variety of market activities and trading strategies; it can be used for market making, collateral transformation, speculation, hedging and arbitrage. Securities lending can generate and spread risks in the financial system because of the levered interconnections it creates among participants; these risks are mitigated and managed through a range of regulation.
Keywords: G; G1; G18; G21; G23; 330; Financial institutions; Financial markets; Financial system regulation and policies; Market structure and pricing